In-situ isothermal calorimetry of cement pastes — Unraveling mixer effects, viscous heat dissipation, and heat of hydration - Lange, Tobias; Axthammer, Daniel; Jansen, Daniel; Gädt, Torben (Thermochimica Acta, 2025)
The chemical reactivity of inorganic binders such as Portland cement is frequently studied using isothermal heat flow calorimetry. Most often, water and binder are mixed outside of the calorimeter, and the paste is inserted into the calorimeter after 5 to 10 min at the earliest. Consequently, the heat of early hydration reactions is usually not included in the experimental data. The only way to record the heat of hydration from the first contact of water with the binder is to use custom-built internal mixing devices. For this purpose, different mixers have been reported. However, their reliability has yet to be studied and compared systematically. This study compares three internal mixer designs regarding the early heat flow, experimental repeatability, and mixing quality at different water-to-cement ratios. Finally, we study the phase composition of the cement before and during hydration using quantitative X-ray diffraction. Combining the experimental Rietveld data with thermodynamic modeling demonstrates that the observed experimental heat after 60 min of hydration corresponds to the formation of ettringite from C3A and sulfates, while the contribution of the other cement phases is small.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Ettringite; In-situ mixing; Isothermal heat flow calorimetry; Portland cement